P058 LOW DOSE METHOTREXATE HAS SIMILAR OUTCOMES AS HIGH-DOSE METHOTREXATE IN COMBINATION WITH ANTI-TNF THERAPY IN INFLAMMATORY BOWEL DISEASES. (7th February 2019) - Borren, Nynke Z; Luther, Jay; Colizzo, Francis P; Garber, John J; Khalili, Hamed; Ananthakrishnan, Ashwin
Abstract: Introduction: Methotrexate (MTX) is a well-known immunomodulator in the treatment of inflammatory bowel disease (IBD) and often combined with biological agents. The ideal MTX dose for combination therapy has not been determined. Our aim is to investigate the effect of varying doses of MTX when used with anti-TNF agents in IBD on efficacy and safety outcomes. Methods: This study included patients with Crohn's disease (CD) or ulcerative colitis (UC) receiving care between January 2005 and June 2018. Low-dose MTX was defined as ≤15mg/week and high-dose as >15mg/week. The primary efficacy outcome was a composite of need for IBD-related hospitalization or surgery, steroid initiation, or change of biologic agent within 1 year. Safety outcomes included side effects related to MTX, serious infections, malignancy and need to discontinue MTX therapy within 1 year. Multivariable logistic regression models adjusting for relevant covariates examined the independent association between MTX dose and outcomes. Results: Our study included 222 patients with IBD (163 CD, 59 UC). Just over half were receiving low dose MTX (51%). We found no difference in gender, IBD type, disease location and behavior, disease duration, prior IBD treatments, serum albumin and CRP between the two groups. The primary efficacy composite outcome was noted in 51 patients (47%) in the high dose MTX group compared to 47 patients (42%) in the low-dose MTX group (p=0.436). After adjusting for relevant confounders, there remained no difference in primary outcome between the two dose groups of MTX (OR 0.62, 95% CI 0.31 – 1.24, p=0.179). Separately, we also observed no difference in hospitalization, surgery or steroid initiation within 1 year between the low-dose and high-dose MTX groups (Figure 1). MTX dosage was not associated with likelihood of side effects (high dose 22.9% vs low dose 27.4%, p=0.44). A total of 20 serious infections (9%) were reported during the first year of combination therapy but there was no significant difference between high versus low dose MTX (9.2% vs. 8.9%, p=0.93). We found no significant associations with MTX dose and any side effect (OR 1.34, 95% CI 0.67 – 2.70, p=0.410) or development of serious infections (OR 0.97, 95% CI 0.35 – 2.67, p=0.946). Two cases developed a malignancy (thyroid carcinoma and hepatocellular carcinoma) during the first year of combination therapy, both in the high dose MTX group. Discontinuation of MTX therapy occurred in one fourth of the low dose MTX patients (24.8%) and 29.5% in patients with high dose MTX (p=0.442). Conclusion: Low dose and high dose MTX combination therapy were equally effective and no difference in infection and malignancy rates was observed. There is an important need for prospective trials comparing low and high dose MTX when used in combination with biologic therapy to determine optimal dosing. Figure 1. Comparison of safety (a) and efficacy (b) outcomes between low dose MTX and high dose MTX combination therapy